Ahmad Lutfi Fathullah dan Digitalisasi Ḥadīth di Nusantara - Rahmatullah Rahmatullah (Islamica: Jurnal Studi Keislaman, 2020)
This article aims to discuss the relationship between Ahmad Lutfi Fathullah and digitalization of Ḥadīth in Indonesia. The emergence of digitalization of Ḥadith in Indonesia can be associated with one of the leading scholars in the field of Ḥadīth, namely Ahmad Lutfi Fathullah through the Center of Ḥadīth Studies (PKH). The reason for the efforts of Ḥadīth digitalization by Ahmad Lutfi Fathullah departed from the awareness to maintain the existence of Ḥadīth studies in the modern era that demands the use of technological tools. The effort to digitalize the Ḥadīth as the result of collaboration with the use of technology has now given birth to a variety of digital Ḥadīth products, such as software, websites, android applications and Ḥadīth visualization. The effort to digitalize the Ḥadīth, one of which is undertaken by Ahmad Lutfi Fathullah at this time, has made the tradition of Ḥadīth studies, especially in Indonesia experience a dynamic orientation and transformation of Ḥadīth studies.